PENGARUH KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN E- COMMERCE - Satryawati, Eka (Jurnal Teknologi Informatika dan Komputer, 2018)
E-Com, or ElectronicCommerce is a rapidly evolvingtechnology in the business world and bytheInternet. The use of E-commercesystem, can actually benefit many parties,including the consumer, as well as theproducers and sellers (retailers). Forexample, for the consumer, using the ECommercecan make shopping a shorttime. In addition, the price of the goodssold via E-commerce is usually cheaperthan the prices in the store, because thedistribution of producer goods to the sellershorter than conventional stores.Satisfaction, trust and loyalty DBS is themost important factor in businesscompetition. The four variables that will beused in this research is a web interfacequality, information quality, security andprivacy. This study propose a frameworkmodel or combination of models I.EidMustafa (2011) and model and ParvezAkbar (2009). The hypothesis is useful toexamine the relationship of 4 (four)variables affecting trust, satisfaction andloyalty. The method used is distributingquestionnaires to 200 customers samplesDuta Business School (DBS). Samplesused only 200. Structural Equation Model(SEM) was used to analyze the data. Theanalysis shows that the model does not fitthe model of the population but onlyrepresent a sample. Based on theproposed model, the web interface Qualityand Quality Information positive impact oncustomer satisfaction. Quality webinterface associated with weak consumerconfidence, no information related to thequality of customer confidence, Privacystrongly related to customer trust, securityis closely linked to customer satisfaction.Customer satisfaction affects customerloyalty, customer satisfaction affectscustomer trust.